2016
DOI: 10.18280/ijht.340322
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of Natural Convection in Right-Angled Triangular Enclosures

Abstract: Two-dimensional numerical simulations have been performed to study natural convection in right-angled triangular enclosures filled with water considering different aspect ratios. Continuity, momentum and energy equations are solved assuming Boussinesq approximation utilizing COMSOL. Effect of Rayleigh number, Ra, on heat transfer rate is investigated by showing Nusselt number, Nu, for a range from to . It is shown that increasing aspect ratio of the cavity increases averaged Nusselt number in a cavity heated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The applied voltage ∆V=V0-V1 for the electric potential, ∆V/L for the electric field, q0 for the charge density, ε0K∆ 2 /L 3 for the current density, V/L for the velocity, P0v 2 /L 2 for the pressure, L 2 /v for the time and θ/(θ0-θ1) for the temperature. The above set of coupled equations is solved numerically using the finite element software COMSOL Multiphysics [20][21]. Figure 2 displays the computational mesh.…”
Section: Mathematical Formulation and Numerical Modelmentioning
confidence: 99%
“…The applied voltage ∆V=V0-V1 for the electric potential, ∆V/L for the electric field, q0 for the charge density, ε0K∆ 2 /L 3 for the current density, V/L for the velocity, P0v 2 /L 2 for the pressure, L 2 /v for the time and θ/(θ0-θ1) for the temperature. The above set of coupled equations is solved numerically using the finite element software COMSOL Multiphysics [20][21]. Figure 2 displays the computational mesh.…”
Section: Mathematical Formulation and Numerical Modelmentioning
confidence: 99%
“…They confirmed that in the condition of adding nanoparticle into the main fluid, higher heat exchange and entropy generation is obtained. Mirabedin performed a two‐dimensional numerical simulation to examine natural convection in right‐angled triangular cavities utilizing water, using several aspect ratios. He confirmed that augmenting the aspect ratio augments the mean Nusselt number in a cavity experiencing heating from below.…”
Section: Introductionmentioning
confidence: 99%
“…Mirabedin [3] formulated a correlation for Nusselt number in terms of its aspect ratio and Rayleigh number in case of a triangular enclosure and found that the Nusselt number increased with increase in aspect ratio. Kamiyo et al [4] studied the heat transfer in an asymmetric triangular enclosure with a hot isothermal base wall.…”
Section: Introductionmentioning
confidence: 99%